The effect of sterilization methods on plastics and elastomers. (Plastics Design Library, 1994)
This handbook presents a compilation that illustrates how sterilization methods, and their assistant media, affect the properties and characteristics 69 different plastics and elastomers. The four commonly used methods of sterilization are Ethylene Oxide, Irradiation, Steam and Dry Heat. The data provided ranges from a general overview of the compatibility of various plastics and elastomers to sterilization methods to detailed discussions and test results. Additional data is presented that includes the resistance of plastics and elastomers, chemicals used in sterilization, and other fluids of medical significance. Information for each test is provided, as well as information for many sterilization methods and material combinations. Data appear in textual, tabular, and graphical forms. Tables and graphs provide detailed test results.
Keywords: Polymers in medicine -- Tables.; Polymers -- Chemical resistance -- Tables.; Elastomers -- Chemical resistance -- Tables.; Radiation sterilization -- Tables.; Medical supplies -- Sterilization -- Tables.; Medical instruments and apparatus -- Sterilization -- Tables.; Biomedical materials -- Testing -- Tables.; Biomedical materials -- Effect of radiation on -- Tables.; elektronické knihy; electronic books